1995
DOI: 10.1093/fampra/12.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations: What do primary care patients want from the GP and how far does meeting expectations affect patient satisfaction?

Abstract: There is growing recognition of the importance of patients' expectations in general practice. This study aimed to investigate the types of expectations adult primary care patients have prior to consulting the GP, and how far meeting expectations is associated with increased satisfaction. Patients (n = 504) attending general practitioners (n = 25) at 10 London general practices were included in the study. The Patients Intentions Questionnaire (PIQ) was administered prior to the consultation to investigate patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0
18

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(181 citation statements)
references
References 9 publications
7
156
0
18
Order By: Relevance
“…The results are in accordance with earlier studies concluding that patients' expectations were the best predictor of patient satisfaction 11 and that the extent to which expectations were met influenced the outcome in terms of satisfaction. 7,13 Another study 20 concluded that expectations served as independent predictors of satisfaction but were not associated with patients' age, gender, marital status, or race. Our results, however, suggest that patients' age, gender and education level were the main determinants and were inversely related to patients' preoperative expectations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are in accordance with earlier studies concluding that patients' expectations were the best predictor of patient satisfaction 11 and that the extent to which expectations were met influenced the outcome in terms of satisfaction. 7,13 Another study 20 concluded that expectations served as independent predictors of satisfaction but were not associated with patients' age, gender, marital status, or race. Our results, however, suggest that patients' age, gender and education level were the main determinants and were inversely related to patients' preoperative expectations.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some studies have concluded that levels of satisfaction are not affected by unmet expectations, or that there was little evidence to show that expectations play a significant role in the evaluation of satisfaction with care. [3][4][5] However, others have shown that levels of satisfaction do relate to preoperative expectations 6,7 and may serve as significant predictors of dissatisfaction and mood disturbance. 1,2 In particular, patients' satisfaction or dissatisfaction after spinal surgery has been shown to be influenced by patients' expectations, their medical condition and health status, psychosocial variables, and characteristics of the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patient satisfaction with primary care and general practitioners is strongly influenced by the mode of care delivery, physician style, availability of out-of-hours care, a named physician, continuity of care and provision of routine screening (66,67,68,69).…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Discussing views can lead to greater congruence between patient and practitioner. This is important because congruent views increase patient satisfaction, which is a factor believed to influence the intention to comply [34][35][36].…”
Section: Introductionmentioning
confidence: 99%